2006
DOI: 10.1002/mrm.20988
|View full text |Cite
|
Sign up to set email alerts
|

Proton spectral editing for discrimination of lactate and threonine 1.31 ppm resonances in human brain in vivo

Abstract: Prior 1 H MRS measurements of lactate (Lac) in human brain in vivo commonly focused on the methyl proton resonance at 1.31 ppm. These methyl protons are scalarly coupled to a methine proton resonating at 4.10 ppm, with strength of 6.93 Hz (pH neutral) (1). For detection of this low-concentration metabolite, a doublet at 1.31 ppm is often targeted with either a short TE (2) or an optimized long TE (3) to minimize the spectral overlap with lipid signals. The overlapping interference can be further reduced by spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 19 publications
1
46
2
Order By: Relevance
“…There may also be other coupled species that coedit with lactate, in particular threonine (37). It seems reasonable, however, to assume that the vast majority of the signal in tumors is due to lactate rather than threonine, since glycolytic overdrive has long been recognized as a common feature of tumors (38); however, some contribution of threonine to the edited peak in vivo cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…There may also be other coupled species that coedit with lactate, in particular threonine (37). It seems reasonable, however, to assume that the vast majority of the signal in tumors is due to lactate rather than threonine, since glycolytic overdrive has long been recognized as a common feature of tumors (38); however, some contribution of threonine to the edited peak in vivo cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, spectral overlapping caused by J-coupling can be eliminated to provide spectra with better resolution. Spectral editing techniques can selectively suppress or emphasize certain resonances, and they have been widely used to detect overlapping or hidden signals, such as gamma-aminobutyric acid (GABA),39 glutamine/glutamate,40 and lactate (Lac) 41…”
Section: Possible Strategies For Detecting Npcs In Vivomentioning
confidence: 99%
“…Variants of the same technique were used to detect threonine in vivo in rat (6) and human (7) brains. Recently, a new J ‐difference editing method was used to quantify the threonine concentration in the human brain by discriminating between the lactate and threonine resonance at 1.32 ppm based on selective refocusing of the J ‐coupled partner at 4.11 ppm and 4.24 ppm (8). The results indicated that threonine (0.56 ± 0.06 mM) was present at slightly higher concentration than lactate (0.47 ± 0.07 mM) in the human occipital cortex (8).…”
mentioning
confidence: 99%